3342 Developing a population health learning system. (27th March 2019) - Kuo, Tony; Inkelas, Moira
Abstract : OBJECTIVES/SPECIFIC AIMS: Population health research seeks to identify and address variation in needs, care experiences, and outcomes for a defined geography or subgroup. Solutions often require collective actions of complex interdependent health and social service systems in communities. System sciences focused on implementation and dissemination are vital for developing interventions that work at the intended scale in these "real world" environments; yet these approaches are often underutilized. METHODS/STUDY POPULATION: The UCLA Clinical Translational Science Institute (CTSI) co-developed a Population Health Program with the local health department to advance the practice and use of these system science methods. The vision is integrated training, methodological innovation, and real-world application in the region. One specific aim of the program is preparing investigators to apply suitable translational methods to solve population health problems in both health systems and in public health. Investigators from different parts of the university partnered with health services and public health leadership to develop and team-teach new curriculum in system sciences that integrates their disciplines (epidemiology, education, psychology, health policy and management). RESULTS/ANTICIPATED RESULTS: New curriculum in population and implementation/improvement sciences offers junior investigators effective modules and training opportunities that can support their career awards. The program is also increasing the receptivity and readiness of population health delivery systems to apply system science methods to pressing problems. Program metrics include total participants, research yielded by the collaboration, and skills and system science mindset acquisition among trainees, investigators, and health personnel. DISCUSSION/SIGNIFICANCE OF IMPACT: CTSAs can partner with health and public health agencies to develop shared infrastructure, developing capacity in the university and in the partnered local agencies so that investigators and the agencies that are responsible for population health can work together to apply suitable translational methods to solve population health problems in both health systems and in public health.